Rare cancer with primary pleural epithelioid hemangioendothelioma diagnosed by thoracoscopic biopsy achieving disease control after 16 months: case report and literature review - Pateras, Ioannis S.; Kostopanagiotou, Konstantinos; Samaras, Menelaos G.; Koumarianou, Anna; Koutrouli, Mina; Korodimos, Nikolaos; Kampoli, Katerina; Apollonatou, Vasiliki; Manali, Effrosyni; Loukides, Stylianos; Tomos, Periklis; Tsiodras, Sotirios; et al. (Frontiers in Pharmacology, 2024)
Epithelioid hemangioendothelioma (EHE) is a rare malignant vascular tumor whose pleural EHE (pEHE) type is even more uncommon, with significant heterogeneity in the clinical behavior as well as challenging diagnosis and treatment decisions. Herein, we present a 74-year-old woman admitted to the hospital with dyspnea, pleural effusion, and refractory euvolemic hyponatremia. Chest computed tomography revealed a large right-side pleural effusion with irregular thickening of the parietal pleura and localized nodularity. Histologic evaluation of the thoracoscopic pleural biopsy tissue was used to confirm the diagnosis of pEHE. Assessment of the volume status suggested that the hyponatremia was attributable to a paraneoplastic endocrine syndrome. Administration of the multitarget tyrosine kinase inhibitor pazopanib helped achieve disease control, with the patient remaining free of symptoms after 16 months of follow-up. This case report adds to the knowledge base of this exceptionally rare condition, highlighting the need for a multidisciplinary approach.